Better the devil you know: sympatric fish host copes better than allopatric with a myxozoan parasite - Estensoro, Itziar; López-Gurillo, Beatriz; Tafalla, Carolina; Craig, Ryan; Atkinson, Stephen; Sitjà-Bobadilla, Ariadna; Bartholomew, Jerri (Frontiers in Cellular and Infection Microbiology, 2025)
Ceratomyxosis due to the myxozoan parasite Ceratonova shasta affects salmonids, causing severe enteritis leading to hemorrhaging and necrosis. The waterborne parasite stages penetrate host gills and reach the fish intestine through the bloodstream. Steelhead trout (Oncorhynchus mykiss) populations from C. shasta endemic watersheds (sympatric) are less susceptible than populations from non-endemic watersheds (allopatric). We investigated the immune effectors behind these different susceptibilities. Both steelhead trout strains were exposed to C. shasta genotype 0. Intestinal tissue and serum samples of control and exposed sympatric and allopatric fish were taken at 8, 15, 22, 29, 57, and 183 days post exposure. Gills were taken at 1 and 8 days post exposure. Parasite abundance and histopathology were evaluated on tissue sections of fish that tested PCR+ for the parasite. Zap70+ T cells, IgT+ B cells, and IgD+ B cells were quantified, and the presence of specific IgM was evaluated from fish sera by immunohistochemistry. Parasite counts were significantly lower and limited to a shorter duration in sympatric fish. The initial intestinal inflammatory response in both fish strains was characterized by hyperplasia of the lamina propria–submucosa and epithelial infiltration of lymphocytes. Remarkably, hyperplasia was resolved earlier in sympatric fish, whereas in allopatric fish, hyperplasia was not resolved by the end of the experiment, coinciding with high intestinal parasite counts and sporogenesis. An increase of intestinal Zap70+ T cells occurred before IgT+ B cells peaked, earlier in sympatric than in allopatric fish. Low numbers of intestinal IgD+ B cells were detected in both strains. In gills, an early increase of Zap70+ T cells was observed in both fish strains at 1 day post exposure, and an increase of IgD+ B cells occurred only in the allopatric strain. Specific circulating IgM was detected much later in both fish strains, only at 57 and 183 days post exposure. In conclusion, sympatric steelhead trout restricted intestinal proliferation of C. shasta genotype 0 more effectively than allopatric fish, probably due to an earlier T cell response triggering a stronger IgT-based mucosal adaptive response in the intestine. Specific circulating IgM appeared later in both sympatric and allopatric fish, probably also contributing systemic protection.